CONVERGENCE OF THE STEAM MODEL AND PEDAGOGICAL RESEARCH TO PROMOTE SCIENTIFIC CURIOSITY THROUGH A SYSTEMATIC REVIEW OF THE LITERATURE - Angélica María Loaiza Ortiz; Luis Alberto Avellaneda Caceres; Alix Cristina Rivera Medina (DIALÉCTICA, 2026)
Scientific curiosity in primary education is the fundamental driver of critical thinking development; however, traditional teaching practices often fragment knowledge, restricting students' innate curiosity. The objective of this literature review article was to analyze the convergence between research as a pedagogical strategy and the STEAM approach as a theoretical model for enhancing such curiosity. Methodologically, a descriptive documentary research study was conducted, based on the search, selection, and critical analysis of 17 primary academic sources, most of which were published between 2021 and 2025. The collection process was carried out in indexed databases, prioritizing high-impact articles that allowed for rigorous triangulation. The review showed that the STEAM model transcends the grouping of disciplines, configuring itself as a transdisciplinary ecosystem where the artistic component acts as a bridge to scientific awareness. It was identified that the integration of research in the classroom under this approach stimulates higher cognitive processes by placing students in front of real problems. In conclusion, it is argued that fostering scientific curiosity through the articulation of research and STEAM is imperative to overcome encyclopedic teaching. This combination allows for a transition from reproductive education to training focused on scientific literacy and critical citizenship from an early age. The review highlights a gap in contextualized teaching guides for the Latin American environment, suggesting the need for future lines of research that effectively operationalize these theoretical frameworks in contemporary primary school teaching practice.